2019
DOI: 10.1155/2019/1342549
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Folic Acid Administration on Cardiac Oxidative Stress and Cardiovascular Biomarkers in Diabetic Rats

Abstract: The aim of this study was to examine the effects of folic acid administration on the antioxidant enzyme (superoxide dismutase (SOD) and catalase (CAT)) activities, lactate and malate dehydrogenase (LDH and MDH) activities, and certain LDH and MDH isoform distribution in the cardiac tissue of diabetic Wistar male rats. Diabetes mellitus (DM) was induced by streptozotocin (STZ). There were five groups: C1—control (physiological saline 1 ml/kg, i.p. one day), C2—control with daily physiological saline treatment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…In the current study, elevated activity of cardiac CAT and SOD activities were determined in untreated diabetic rats. These results were similar to the results of other studies [ 32 35 ]. Conversely, some other reports revealed decreased CAT and SOD activities [ 36 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, elevated activity of cardiac CAT and SOD activities were determined in untreated diabetic rats. These results were similar to the results of other studies [ 32 35 ]. Conversely, some other reports revealed decreased CAT and SOD activities [ 36 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress markers were ameliorated by FA supplementation may be due to its direct effect on free-radical oxidation of LDL lipids (Lee et al, 2011). Also, FA has an antioxidant effect, it is reported that its administration decreases the production of ROS (Mutavdzin et al, 2019). The significant result of LE was due to its ability in restoring renal function by restoring antioxidants and preventing cellular damages.…”
Section: Discussionmentioning
confidence: 97%
“…In quail, dietary supplementation of folic acid (2 mg/kg) alleviated the negative effects of CS on growth performance, lipid peroxidation, and serum concentrations of homocysteine (Sahin et al, 2003a). In mouse, administration of folic acid ameliorated the inhibitory effects of HS on the pre-implantation embryos development (Koyama et al, 2012), served a protective role by reducing the CAT, SOD, and glucose level (Padmanabhan et al, 2018;Mutavdzin et al, 2019). The ameliorative effects of vitamin B in chickens challenged with environmental stress are rarely studied.…”
Section: Vitamin Bmentioning
confidence: 99%